2019
DOI: 10.3390/su11236855
|View full text |Cite
|
Sign up to set email alerts
|

Role of Waste Collection Efficiency in Providing a Cleaner Rural Environment

Abstract: The exposure of rural communities to illegal waste dumping practices associated with the lack of or poor waste collection schemes prior to the closure of rural dumpsites under EU regulations and the role of collection efficiency afterward in reducing this critical environmental threat constitutes a key issue in rural Romania. The present study reveals huge amounts of household uncollected waste released into the natural environment outside the official statistics of rural dumpsites. Despite the expansion of wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Local authorities are responsible to collect and properly dispose of such wastes. Uncontrolled waste disposal practice is a serious environmental issue in Romania where peri-urban and rural regions are the most exposed to such practices [ 15 ]. Each spring season, the local authorities must perform sanitation activities around their localities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local authorities are responsible to collect and properly dispose of such wastes. Uncontrolled waste disposal practice is a serious environmental issue in Romania where peri-urban and rural regions are the most exposed to such practices [ 15 ]. Each spring season, the local authorities must perform sanitation activities around their localities.…”
Section: Resultsmentioning
confidence: 99%
“…Romania is coping with several mismanagement practices such as poor efficiency of source-separated waste collection schemes in urban areas, the prevalence of landfills as a main waste management option, delays in implementation of regional integrated waste management systems, lack of a reliable waste statistics database, etc. Furthermore, rural Romania is facing illegal waste disposal practices (wild dumps, open burning practices), plastic pollution of freshwater bodies and limited waste collection coverage of the rural population in some counties [ 14 , 15 ]. The circular economy remains underdeveloped despite the promising potential in this area [ 16 ], but the new circular economy plan promoted EU could catalyze the effort in the right direction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, other studies observed that having environmental education improves the residents' sense of environmental protection awareness. This also includes understanding the benefits of collecting and classifying rural wastes in their day-to-day life [13,25]. Therefore, the more learned an individual is, the higher environmental protection awareness they have.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the environment is conserved and protected as the residents dump the available household wastes in the right waste bins after classification. Further, the availability of the waste bins within the rural areas conveniences the rural residents and improves the frequency of cleaning and classification [13]. Even more, it increases the likelihood of attending to environmental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation